Life in a drop: Sampling environmental DNA for marine fishery management and ecosystem monitoring. (February 2021) - Gilbey, John; Carvalho, Gary; Castilho, Rita; Coscia, Ilaria; Coulson, Mark W.; Dahle, Geir; Derycke, Sofie; Francisco, Sara M.; Helyar, Sarah J.; Johansen, Torild; Junge, Claudia; Layton, Kara K.S.; et al.
Abstract: Science-based management of marine fisheries and effective ecosystem monitoring both require the analysis of large amounts of often complex and difficult to collect information. Legislation also increasingly requires the attainment of good environmental status, which again demands collection of data to enable efficient monitoring and management of biodiversity. Such data is traditionally obtained as a result of research surveys through the capture and/or visual identification of organisms. Recent years have seen significant advances in the utilisation of environmental DNA (eDNA) in the marine environment in order to develop alternative cost-effective ways to gather relevant data. Such approaches attempt to identify and/or quantify the species present at a location through the detection of extra-organismal DNA in the environment. These new eDNA based approaches have the potential to revolutionise data collection in the marine environment using non-invasive sampling methods and providing snapshots of biodiversity beyond the capacity of traditional sampling. Here we present a non-technical summary of different approaches in the field of eDNA, and emphasise the broad application of this approach, with value for the governance and management of marine aquatic ecosystems. The review focuses on identifying those tools which are now readily applicable and those which show promise but are currently in development and require further validations. The aim is to provide an understanding of techniques and concepts that can be used by managers without genetic or genomic expertise when consulting with specialists to perform joint evaluations of the utility of the approaches. Highlights: Non-technical summary of environmental DNA use for management of marine ecosystems. Marine community characterisation using environmental DNA. Marine abundance estimates using environmental DNA. Integration of DNA based approaches into routine ecosystem monitoring.